2023
DOI: 10.1073/pnas.2301608120
|View full text |Cite
|
Sign up to set email alerts
|

Associations between light exposure and sleep timing and sleepiness while awake in a sample of UK adults in everyday life

Altug Didikoglu,
Navid Mohammadian,
Sheena Johnson
et al.

Abstract: Experimental and interventional studies show that light can regulate sleep timing and sleepiness while awake by setting the phase of circadian rhythms and supporting alertness. The extent to which differences in light exposure explain variations in sleep and sleepiness within and between individuals in everyday life remains less clear. Here, we establish a method to address this deficit, incorporating an open-source wearable wrist-worn light logger (SpectraWear) and smartphone-based online data collection. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Another limitation of the demonstrated procedure is that it only applies to changes in metrics or (with slight adjustments) distributions of metrics, derived by from light exposure measurement. Many studies connect light exposure (and derived metrics) to other quantities or constructs, like sleep, alertness or mental health [11,13,14], and those other quantities will not be available in most datasets. A more theoretical approach for power estimation will be required there, such as described by Kumle, et al [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the demonstrated procedure is that it only applies to changes in metrics or (with slight adjustments) distributions of metrics, derived by from light exposure measurement. Many studies connect light exposure (and derived metrics) to other quantities or constructs, like sleep, alertness or mental health [11,13,14], and those other quantities will not be available in most datasets. A more theoretical approach for power estimation will be required there, such as described by Kumle, et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…Developments in the eld of miniaturized sensor platforms have reduced the cost and size of these devices, while computational power and interfaces improved. We see a surge in studies using wearable light sensors in recent years, which is likely fueled by these developments in combination with increasing interest from the scienti c community [1,[11][12][13][14][15][16]]. This trend is likely to continue and bring new challenges for researchers working on the non-visual effects of light.…”
Section: Introductionmentioning
confidence: 99%
“…A simple design could integrate a spectrophotometer with suitable data processing capacity. Alternatively, cheap multichannel light sensors, which are increasingly being applied to measure human α-opic irradiances [ 47 49 ], could be recalibrated to measure species-specific metrics [ 46 ]. Examples of commercially available light meters and spectrophotometers are provided in S2 Table .…”
Section: Guidance For Measuring α-Opic Quantities In Practicementioning
confidence: 99%
“…These metrics can subsequently be linked to health outcomes of interest (Spitschan et al, 2022). For example, field studies using wrist-worn light loggers have shown an association between greater light exposure before sleep with lower self-reported alertness during the day (Didikoglu et al, 2023), poorer objective sleep quality (Cain et al, 2020), differences in sleep-wake consolidaton (Lok et al, 2023), and altered sleep architecture (Wams et al, 2017). Furthermore, higher light exposure during sleep has been linked to later sleep offset and poorer sleep continuity (Mead et al, 2023).…”
Section: Introductionmentioning
confidence: 99%